MOVING THE EARLY CHILD DEVELOPMENT AGENDA FROM THE PERIPHERAL TO THE CENTER OF DEVELOPMENTAL INITIATIVES: THE NEW AFRICAN PERSPECTIVE ON EARLY CHILD HOOD DEVELOPMENT IN AFRICA - Sophie Sithole, Tholiwe; Linkie Linchwe, Boang (The journal of contemporary issues in business and government, 2022)
Fundamentally, quality early learning programmes prepare children for adulthood, providing them with the necessary opportunities for social, cognitive, spiritual, physical and emotional development. Africa has for a long time been disadvantaging its own young people by not providing adequate resources for the care and education of young children. Some of this emanates from long historical ties and experiences deliberately created during colonialism.Colonialism and the resultant socioeconomic suffering of young children are a matter of consideration. Inequalities did create a childhood of adversity for most black African children across the continent, including inadequate access to health care, education, social services and quality nutrition. This has and continues to;undennine the development of our children. It is however important to note that, to a large extent, we need to take hats off to most African states for their continued attempt to transform their education system by moving the young children from the peripheral to the center of educational development. This is despite the presents of socio-economic barriers which disable full execution of their policies on Early Childhood Education and Development.